2011
DOI: 10.1177/1029864911423161
|View full text |Cite
|
Sign up to set email alerts
|

Musical and non-musical involvement in daily life: The case of absorption

Abstract: The construct of absorption (effortless engagement) has been the subject of a small number of discipline-specific studies of involvement, including music. This paper reports the results of an empirical project that compared psychological qualities of absorption in everyday music listening scenarios with characteristics of non-music-related involvement. Absorption was located in “real-world” settings, and experiences across different activities in a variety of contexts were tapped as soon as possible after they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 59 publications
1
35
0
2
Order By: Relevance
“…One exception to this is absorption, which is linked to the personality trait of openness to experience. Herbert [3] found that engagement with music is an important way of inducing absorption, making the study of music and absorption particularly appealing. Thus, in this study we investigated the relationships between music preference and trait versus state absorption.…”
Section: Introductionmentioning
confidence: 99%
“…One exception to this is absorption, which is linked to the personality trait of openness to experience. Herbert [3] found that engagement with music is an important way of inducing absorption, making the study of music and absorption particularly appealing. Thus, in this study we investigated the relationships between music preference and trait versus state absorption.…”
Section: Introductionmentioning
confidence: 99%
“…None expressed feeling self-conscious. This appears to mirror a stream of prior research on everyday mobile music listening [6,19], which emphases its dissociative function in which people immerse themselves in personalised 'soundworlds', experiencing feelings of accompanied isolation, control, selfsufficiency, an even a form of sanctuary [6].…”
Section: Accompanied Solitudementioning
confidence: 98%
“…Similar is Chion's concept of conceptual resonance, a cyclical process in which music affects a viewer's interpretation of an image, which in turn affects their impression of the music [8]. Shifting to mobile music listening, Bull and Herbert present spreading activation to account for how iPod's 'astheticise' their environment and in doing so improve the quality of their experience [6,19].…”
Section: Emotional Enhancementmentioning
confidence: 99%
See 2 more Smart Citations